Facile fabrication of hyper-branched TiO2 hollow spheres for high efficiency dye-sensitized solar cells. (1st November 2018) - Marandi, M.; Bayat, S.
Highlights: Branched TiO2 HSs were synthesized via a hydrothermal process using TiO2 HSs. The hydrothermal time was altered to control the morphology of the branched TiO2 HSs. TiO2 HSs and branched HSs were applied in the light scattering layer of the DSCs. The DSC with branched TiO2 HSs prepared in 2 h of heating time showed a PCE of 9.85% This efficiency was enhanced about 9% compared to that of the DSC with just TiO2 HSs. Abstract: TiO2 hollow spheres (HSs) with external diameters around 430 nm were prepared using carbon spheres as the templates. Then they were introduced to another hydrothermal process for branching. TiCl3 was used as the Ti source in this stage and hydrothermal time was changed in a wide range. Conic branches were grown on the surface of the TiO2 HSs while the spherical shapes were quite preserved. The base diameter and height of the TiO2 branches were controlled by autoclaving time. Three different photoanodes were fabricated and applied in dye-sensitized solar cells (DSCs). The first one was a single-layer photoanode composed of hydrothermally grown TiO2 nanocrystals (NCs) with dominant size of 25 nm. The second electrode was a nanocrystalline TiO2 layer covered by a TiO2 HSs light scattering layer. The third type was a double-layer photoanode composed of TiO2 NCs sub-layer and hyper-branched TiO2 HSs over-layer. The influence of the morphology of the grown branches on the photovoltaic performance of the DSCs was investigated and discussed. A maximum energy conversion efficiency of 9.85% was achieved for the pioneer cell through the optimization of the branching process. This efficiency was increased about 39% and 9% compared to those of the DSCs with TiO2 NCs and TiO2 NCs/TiO2 HSs photoelectrodes. The reason was attributed to the increased amount of dye adsorption and light scattering of the optimized cell due to the applied hyper-branched TiO2 HSs.